Policy to support scientific research and technology development activities in the world and lessons learned for Vietnam - Nguyen Dang Nui (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
In the process of industrialization, modernization, science and technology (S&T) are important resources for the development of a country. In Vietnam, many policies supporting scientific research and technological development have been planned, organized, and implemented, but there are still limitations that need to be addressed to meet the country's development goals. Research is conducted with a focus on analyzing the experiences of S&T development support policies worldwide, especially in some developed economies. Based on the research results, the authors propose some suitable recommendations for Vietnam's future development. Code: 23101702